Comprehensive Evaluation of CNC Machine Tools Accuracy Based on AHP - ZhiMing Feng; Guofu Yin; Haifeng Lin; Xiaxia Gong (Institute of Advanced Engineering and Science, 2014)
In order to evaluate the accuracy of a numerical control machine tool comprehensively, the accuracy evaluation index system of a numerical control machine tool was established, and the priorities of accuracy indexes were determined by analytic hierarchy process method. Taking a five-axis numerical control machine tool for example, each accuracy index of it was studied by using fuzzy comprehensive evaluation, and a membership function was constructed by the intermediate form trapezoidal distribution. The evaluated result indicated that the accuracy of this numerical control machine tool was excellent. As a reference, the method presented in this paper could be used to evaluate the accuracy of other numerical control machine tools. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.3715